Evaluating the sensitivity and influential factors of freeze-thaw erosion in Tibet, China - Fan, Jianrong; Xu, Fubao; Zhang, Xiyu; Zhang, Xiaoxue; Liang, Bo (Frontiers in Earth Science, 2022)
Freeze‒thaw (FT) erosion has gradually become more severe due to climate warming, and concerns about FT erosion in ecologically fragile areas (e.g., high-altitude and high-latitude areas) continues to grow. Tibet, located at the Third Pole of Earth, is also in a substantial part underlain with seasonally frozen soil and subject to FT erosion. Evaluating the sensitivity and influential factors of FT erosion in Tibet is warranted to manage the ecological environment and human production activities. In this study, we investigated the sensitivity and spatial distribution characteristics of FT erosion in Tibet based on advanced remote sensing and geographic information system (GIS) technologies. To further explore the influence of each factor on FT erosion, we analyzed the sensitivity of FT erosion under each factor condition. Our results showed that the annual temperature range is the most influential factor on FT erosion among temperature, precipitation, topography and vegetation. In addition, we introduced the coefficient of variation (CV) to represent the stability of temperature and then used CMIP5 simulation data to estimate the susceptibility of FT erosion in Tibet over the next 30 years. The CVs in central and western Tibet were higher than those in other areas and thus need more attention to FT erosion in central and western Tibet in the future.